Influence of sowing time productivity of green mass of Sudan grass dry steppe zone in northern Kazakhstan (Mongolian Journal of Agricultural Sciences, 2014)
In this article we analyze the effect of sowing date on yield of Sudan grass green mass. The study was conducted over 2 years on the basis of working farms in the dry steppe zone of Kazakhstan. The yield of Sudan grass green mass is depending on the most favorable sowing dates. DOI: http://dx.doi.org/10.5564/mjas.v11i2.219 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.63-67